Risk factors for unplanned weaning of continuous renal replacement therapy in ICU patients: a meta-analysis - Zhi Zeng; Yuqi Shen; Li Wan; Xiuru Yang; Zhenghua Liang; Mei He (Renal Failure)
Objective To systematically review the risk factors for unplanned weaning during continuous renal replacement therapy in ICU patients.Methods A combination of subject words + free words was used to search the relevant literature published in CNKI, Wanfang, VIP, CBM, PubMed, EMbase, Web of Science, Cochrane Library, Mediline and other databases. The search period was from the establishment of the databases to June 25, 2024. Revman 5.4 software and Stata15.0 software was used to meta-analyze the risk factors for unplanned weaning during continuous renal replacement therapy in ICU patients.Results A total of 23 studies were included in this meta-analysis, describing 15 variables, 3793 patients, and using 7197 filters. Meta-analysis results showed that risk factors for unplanned weaning during continuous renal replacement therapy in ICU patients were as follows: Low mean arterial pressure [OR = 1.02, 95%CI (1.00, 1.03), p < 0.05], hypothermia [OR = 3.40, 95%CI (1.78, 6.47), p < 0.05], age (≥60 years) [OR = 4.45, 95%CI (3.18, 6.22), p < 0.05], comorbid underlying disease [OR = 3.63, 95%CI (2.70, 4.88), p < 0.05], agitation [OR = 4.97, 95%CI (3.20, 7.74), p < 0.05], no anticoagulant use [OR = 1.65, 95%CI (1.25, 2.17), p < 0.05], short activated partial prothrombin time [OR = 1.23, 95%CI (1.13, 1.34), p < 0.05], hyper-hematocrit [OR = 1.73, 95%CI (1.13, 2.66), p = 0.01], low ionized calcium concentration [OR = 1.48, 95% CI (1.08, 2.02), p = 0.01], CRRT that was treated at a high dose [OR = 1.42, 95%CI (1.14, 1.76), p < 0.05], mechanical ventilation [OR = 4.25, 95%CI (2.67, 6.77), p < 0.05], and lack of dedicated care [OR = 5.08, 95%CI (2.51, 10.28), p < 0.05]. However, it is unclear whether platelet count, prothrombin activity, and blood flow velocity are risk factors for unplanned weaning during CRRT in ICU patients, and more studies are needed for further validation.Conclusion Available evidence suggests that a variety of factors contribute to unplanned weaning of CRRT in ICU patients. Early detection of these risk factors is essential for healthcare professionals to develop preventive and curative strategies.Registration This study is registered on the PROSERO website under registration number CRD42024543554.